2019
DOI: 10.1097/ogx.0000000000000738
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Migraine and Adverse Pregnancy Outcomes: Systematic Review and Meta-analysis

Abstract: Importance Migraine is a highly prevalent disorder associated with cardiovascular diseases. Cardiovascular diseases are also associated with preeclampsia (PE). The adverse pregnancy outcomes PE, preterm birth (PTB), low birth weight (LBW), small for gestational age (SGA) and placental abruption share aspects in their pathophysiology, which are also found in patients with migraine, such as inflammatory stress and hypercoagulability. Objective To determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 41 publications
5
41
1
2
Order By: Relevance
“…However, we found that women with migraine appear to have a slightly increased risk of preeclampsia and low birthweight deliveries. 22,36-38 Our findings further illustrated an increased risk of fetal stress, labor and delivery complications, and the presence of a CDC SMM indicator.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, we found that women with migraine appear to have a slightly increased risk of preeclampsia and low birthweight deliveries. 22,36-38 Our findings further illustrated an increased risk of fetal stress, labor and delivery complications, and the presence of a CDC SMM indicator.…”
Section: Discussionsupporting
confidence: 62%
“…We identified clinical and obstetric factors associated with increased maternal morbidity and mortality from previous studies. 2,[13][14][15][16][17][18][19][20][21][22][23][24] Obstetric characteristics of interest included the validated CDC SMM indicators. 2,13,14,18,25 The 21 SMM indicators include serious labor and delivery outcomes that are identifiable at delivery hospitalization using ICD-10 procedure and diagnosis codes and provide a standardized tool to track acute peripartum complications that may result in significant short-or long-term maternal health sequelae (e.g., cardiac arrest, eclampsia, sepsis).…”
Section: Covariatesmentioning
confidence: 99%
“…Vigilance in the prenatal care provided to patients with a history of migraine is also important because the underlying physiology associated with migraine increases the risk of preeclampsia and other hypertensive disorders (odds ratio [OR] 2.07; 95% CI 1.51–2.85) (21) and (OR 2.85; 95% CI 1.40–5.81) (22) compared with those without migraine. The associated risks of low birthweight (OR 1.18; 95% CI 1.03–1.34) (21) and (OR 1.97; 95% CI 0.98–3.98) (22) as well as preterm birth (OR 1.23; 95% CI 0.97–1.55) (21) and (OR 1.16; 95% CI 1.07–1.24) (23) are less conclusive.…”
Section: Clinical Overviewmentioning
confidence: 99%
“…Altogether, these studies suggest that hypertensive disorders, such as preeclampsia [18] and infections (most commonly viral infections and sinusitis) [4] are the most common causes of SHDs. It is important to emphasize that the hypercoagulable state caused by pregnancy [2,10] and migraine [20] are independent risk factors for preeclampsia, cerebral venous thrombosis, TIA and stroke [8,9]. Two retrospective studies reported that specific clinical findings, so-called "red flags" (Table 3) [4,18], should alarm doctors to investigate for the underlying cause of SHD.…”
Section: Discussionmentioning
confidence: 99%